The detection and characterization of pathogenic Leptospira and the use of OMPs as potential antigens and immunogens. - Gebriel, A.M.; Subramaniam, G.; Sekaran, S.D. (2006)
The detection of leptospires in patient blood in the first week of the disease using PCR provides an early diagnostic tool. PCR using two sets of primers (G1/G2 and B64-I/B64-II) tested with samples seeded with 23 leptospiral strains from pathogenic and non-pathogenic strains was able to amplify leptospiral DNA from pathogenic strains only. Of the 39 antibody negative samples collected from patients suspected for leptospirosis, only 1 sample (2.6%) was PCR positive. Using LSSP-PCR, the G2 primers allowed the characterization of Leptopira species to 10 different genetic signatures which may have epidemiological value in determining species involved in outbreaks. Leptospiral outer membrane proteins from three strains were purified and reacted against patients sera and gave rise to different profiles for pathogenic and non-pathogenic strains. Lymphocytes of mice injected with OMPs proliferated and released IFN(-3) when stimulated in vitro using Leptospira OMP as antigens. This suggests that an immune response could be established using leptospiral OMPs as a putative vaccine. OMPs were also used in a Dot-ELISA to detect antibodies against Leptospira pathogens in humans.